2022
DOI: 10.1021/acsomega.2c03331
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Process and Microbial Evolution in the Conversion of Corn Straw Combined with Coal to Biogas

Abstract: The combined anaerobic fermentation of coal and straw can increase the production of biogas. To explore the mechanism of adding corn straw to increase methane production, coal with different metamorphic degrees and corn straw were collected for biogas production simulation experiments under different substrate ratios. The changes in liquid products, the structure of lignocellulose in corn straw, and microbial evolution were monitored. The results showed that the combined fermentation of bituminous coal A with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Therefore, many studies have demonstrated that temperature has an effect on the community composition of microorganisms during anaerobic fermentation, but the metabolic pathways of methanogenesis are different under different operating conditions and raw materials. Most of the research works have focused on the exploration of the effect of fermentation temperature on the larger VS of substances such as kitchen waste, 19 pig manure, 13 straw, 14,20,21 sewage sludge, 22,23 and so forth, and few studies have reported the effect of temperature on the fermentation properties and microbial community when low VS of wastewater such as poplar ethanol wastewater was treated by AD. The objective of this study was to compare the fermentation performance of poplar ethanol wastewater (smaller VS compared to other substrates) at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies have demonstrated that temperature has an effect on the community composition of microorganisms during anaerobic fermentation, but the metabolic pathways of methanogenesis are different under different operating conditions and raw materials. Most of the research works have focused on the exploration of the effect of fermentation temperature on the larger VS of substances such as kitchen waste, 19 pig manure, 13 straw, 14,20,21 sewage sludge, 22,23 and so forth, and few studies have reported the effect of temperature on the fermentation properties and microbial community when low VS of wastewater such as poplar ethanol wastewater was treated by AD. The objective of this study was to compare the fermentation performance of poplar ethanol wastewater (smaller VS compared to other substrates) at different temperatures.…”
Section: Introductionmentioning
confidence: 99%